Effect of Plumeria alba’s bioactive extract against colletotrichum gleosporoides in vitro and in vivo - Mohamad Nor, Maryan; Mohd Hassan, Husna Hawa; Nik Mohamad Ravi, Nik Hairiah; Omar, Muhammad Nor (David Publishing Company., 2014)
Abstract: Plant species in the genus Plumeria of Apocynaceae family are well known for their uses in traditional medicine antimicrobial activity. Plant materials from P. alba were extracted using Soxhlet apparatus and screened for the control of anthracnose disease caused by Colletotrichum gleosporoides on fruit during post harvest storage. For in vitro, the crude extract of P. alba (stem bark and leaves) were completely inhibited conidial germination (sporulation test method) of Colletotrichum gleosporoides at all concentration tested except the lowest concentration (4.4 uL). In vivo studies show that percentage of infection on fruit after treated with both stem bark (11.11 + 3.8) and leaves (15.55 + 3.8) part, at 32,000 mg/L have no significant differences during seven days of storage at ambient temperatures. These results proved that P. alba extracted (stem bark and leaves) were found to be promising as an antifungal agent and to control anthracnose disease in fruits tested.